Willingness to volunteer among remote workers is insensitive to the team size - Adrian Hillenbrand; Tobias Werner; Fabian Winter (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2022)
Volunteering is a widespread allocation mechanism in the workplace. It emerges naturally in software development or the generation of online knowledge platforms. Using a field experiment with more than 2000 workers, we study the effect of team size on volunteering in an online labor market. In contrast to our theoretical predictions and previous research, we find no effect of team size on volunteering although workers react to free riding incentives. We replicate the results and provide further robustness checks. Eliciting workers' beliefs about their co-workers' volunteering reveals conditional volunteering as the primary driver of our results.
Keywords: C72; C93; H41; J4; 330; volunteering; "volunteer's dilemma"; remote work; team size